Evaluation of geometrical precision and surface roughness quality for the additively manufactured radio frequency quadrupole prototype. Issue 1 (1st January 2023) - Torims, T; Cherif, A; Delerue, N; Pedretti, M Foppa; Krogere, D; Otto, T; Pikurs, G; Pozzi, M; Ratkus, A; Thielmann, M; Vedani, M; Vretenar, M; et al.
Abstract: A multidisciplinary collaboration within the I.FAST project teamed-up to develop additive manufacturing (AM) technology solutions for accelerators. The first prototype of an AM pure-copper Radio Frequency Quadrupole (RFQ) has been produced, corresponding to ¼ of a 4-vane RFQ. It was optimised for production with state-of-the-art laser powder bed fusion technology. Geometrical precision and roughness of the critical surfaces were measured. Although the obtained values were beyond standard RFQ specifications, these first results are promising and confirmed the feasibility of AM manufactured complex copper accelerator cavities. Therefore, further post-processing trials have been conducted with the sample RFQ to improve surface roughness. Algorithms for the AM technological processes have also been improved, allowing for higher geometrical precision. This resulted in the design of a full 4-vane RFQ prototype. At the time of the paper submission the full-size RFQ is being manufactured and will undergo through the stringent surface quality measurements. This paper is discussing novel technological developments, is providing an evaluation of the obtained surface roughness and geometrical precision as well as outlining the potential post-processing scenarios along with future tests plans.